The developing human clinically oriented embryology - Moore, Keith L. (Saunders/Elsevier, 2013)
Delivers clinically oriented coverage of embryology. This title presents week-by-week and stage-by-stage views of how fetal organs and systems develop, why and when birth defects occur, and what roles the placenta and fetal membranes play in development.